1-Zirconacyclobuta-2, 3-dienes: synthesis of organometallic analogs of elusive 1, 2-cyclobutadiene, unprecedented intramolecular C–H activation, and reactivity studies. Issue 48 (1st December 2021) - Shi, Xinzhe; Li, Sihan; Reiß, Melanie; Spannenberg, Anke; Holtrichter-Rößmann, Thorsten; Reiß, Fabian; Beweries, Torsten
Abstract : A detailed study of structure, bonding and reactivity of new 1-zirconacyclobuta-2, 3-dienes is presented in comparison to a lighter Ti analog. We found a unique C–H activation at the widely used rac -(ebthi) ligand for that only occurs for Zr. Abstract : The structure, bonding, and reactivity of small, highly unsaturated ring systems is of fundamental interest for inorganic and organic chemistry. Four-membered metallacyclobuta-2, 3-dienes, also referred to as metallacycloallenes, are among the most exotic examples for ring systems as these represent organometallic analogs of 1, 2-cyclobutadiene, the smallest cyclic allene. Herein, the synthesis of the first examples of 1-zirconacyclobuta-2, 3-dienes of the type [Cp′2 Zr(Me3 SiC3 SiMe3 )] (Cp′2 = rac -(ebthi), (ebthi = 1, 2-ethylene-1, 1′-bis(η 5 -tetrahydroindenyl)) (2a ); rac -Me2 Si(thi)2, thi = (η 5 -tetrahydroindenyl), (2b )) is presented. Both complexes undergo selective thermal C–H activation at the 7-position of the ansa -cyclopentadienyl ligand to produce a new type of "tucked-in" zirconocene system, 3a and 3b, that possesses a η 3 -propargyl/allenyl ligand. Both types of complexes react with carbonyl compounds, producing enynes in the case of 2a and 2b, as well as η 1 -allenyl complexes for 3a and 3b . Computational analysis of the structure and bonding of 2a and 3a reveals significant differences to a previously described related Ti complex. All complexes were fully characterised, including X-ray crystallography and experimental results were supported by DFT analysis.